First record of a Xenophyophore (Rhizaria: Foraminifera) on the Chilean margin - Araya, Juan Francisco; Gooday, Andrew J. (Zootaxa, 2018)
Xenophyophores are a group of large foraminifera, confined to deep-sea habitats below ~500 m, whose often fragile agglutinated tests may attain sizes up to 10–15 cm or more; their agglutinated tests incorporate a variety of foreign particles (termed ‘xenophyae’), including mineral particles, foraminiferan and radiolarian tests, diatom frustules and sponge spicules, and form structures ranging from simple tubes, plates and rounded lumps to complex folded, branching or reticulated formations (Tendal, 1972). Xenophyophores are widely distributed around the world, particularly in the Pacific and Atlantic Oceans with comparatively few records from the Indian Ocean and from Arctic and Antarctic seas; they occur at all depths in the oceans from ~500 m to >10,900 m (Tendal, 1972, 1996) and are particularly abundant in regions of high surface production, for example beneath upwelling zones, or on seamounts and sloped topography where particle flux is high (Levin and Gooday, 1992). There are scant records regarding xenophyophores in the SE Pacific. Species of the order Stannomida are recorded from the Ecuador and Peru margins (north of ~12°S) (Tendal 1972: Figs 18, 19), while species of the order Psamminida are common in the DISCOL experimental area of the Peru Basin (~7° 4ˈS, 88° 28’W; ~4150 m depth). Maybury and Evans (1994) illustrated two specimens of an undescribed Psammina species collected during the 1989 DISCOL campaign, but otherwise these collections remain largely unpublished.